Joining of TiAl to Steel by Diffusion Bonding with Ni/Ti Reactive Multilayers - Simoes, S (2016)
Dissimilar diffusion bonds of TiAl alloy to AISI 310 stainless steel using Ni/Ti reactive multilayers were studied in this investigation. The Ni and Ti alternating layers were deposited by d.c. magnetron sputtering onto the base materials, with a bilayer thickness of 30 and 60 nm. Joining experiments were performed at 700 and 800 degrees C for 60 min under pressures of 50 and 10 MPa. The effectiveness of using Ni/Ti multilayers to improve the bonding process was assessed by microstructural characterization of the interface and by mechanical tests. Diffusion bonded joints were characterized by scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), electron backscatter diffraction (EBSD), transmission electron microscopy (TEM) and selected area electron diffraction (SAED), high resolution TEM (HRTEM) and Fast Fourier transform (FFT). The bonding interfaces are thin (approximately 5 mu m thick) with a layered microstructure. For all joints, the interface is mainly composed of equiaxed grains of NiTi and NiTi2. The thickness and number of layers depends on the joining conditions and bilayer thickness of the multilayers. Mechanical characterization of the joints was performed by nanoindentation and shear tests. Young's modulus distribution maps highlight the phase differences across the joint's interface. The highest shear strength value is obtained for the joint produced at 800 degrees C for 60 min under a pressure of 10 MPa using Ni/Ti multilayers with 30 nm of bilayer thickness.